Paradoxical bradycardia during surgical caudal vena cava occlusion in an anesthetized dog. Issue 2 (10th January 2017) - Davis, Jennifer; Raisis, Anthea L.; Haitjema, Hildegriet; Drynan, Eleanor A.; Hosgood, Giselle L.
Abstract: Objective: To describe the anesthetic management of a dog undergoing caudal vena cava (CVC) occlusion during adrenalectomy, and to discuss a reflex bradycardia that was observed during the procedure. Case Summary: General anesthesia of a 10‐year‐old Rhodesian ridgeback for excision of an adrenal mass and associated CVC tumor thrombus was performed. The dog was premedicated with IV methadone and anesthesia was induced with IV alfaxalone and maintained with isoflurane in 100% oxygen. An IV remifentanil infusion was administered for intraoperative analgesia. Surgical removal of the thrombus necessitated temporary complete occlusion of the CVC. During CVC occlusion an acute paradoxical bradycardia occurred, which was successfully treated with IV atropine. The cardiovascular change resembled a Bezold–Jarisch or reverse Bainbridge reflex, and was believed to be mediated by cardiac mechanoreceptors following the sudden decrease in preload. Increased myocardial contractility subsequent to increased sympathetic nervous system activity may also have contributed. A decrease in urine output was observed following CVC occlusion but had returned to normal 2 hours following the end of anesthesia. Recovery from anesthesia was otherwise uneventful. New or unique information provided: Although the mechanism is unclear, a paradoxical bradycardia may occur during complete CVC occlusion in the dog. Factors that increase sympathetic nervous system outflow, such as administration of dopamine, may have contributed to the occurrence of the reflex.